DEVELOPMENT OF COGNITIVE ASPECTS OF CHILDREN IN MATCHING NUMBERS WITH NUMBER SYMBOLS USING A COMBINATION OF DEMONSTRATION, MAKE A MATCH MODELS ASSISTED BY AUDIO VISUAL MEDIA - Hidayat, Asrul; Hadi, Sutarto; Darmiyati (Journal of K6, Education and Management, 2019)
The purpose of this study was to describe teacher activities, children's activities and the development of children's cognitive abilities in matching numbers with number symbols using a combination of Demonstration, make a Match model, assisted by Audio-Visual Media in group B of TK RA Citra Islami Banjarmasin. This study uses a qualitative approach with a type of classroom action research (CAR). Sources of data in this study were teacher and child group B of TK RA Citra Islami Banjarmasin located on Jalan Kelayan B Komplek 10 Gang H. Thaberi RT. 13 Banjarmasin. The research instrument used by researchers to retrieve data is observation. The results of this study illustrate that the teacher's activities have been carried out according to the steps that have been set with very good criteria. Child activity increases in each cycle with very active criteria. Development of cognitive aspects of children in matching numbers with number symbols using a combination of Demonstration, make a Match model, assisted by Audio-Visual Media in group B TK RA Citra Islami Banjarmasin has improved with the criteria of developing very well. The suggestion of this study is expected to be a guideline in learning activities using the combined Demonstration, Make a Match model, assisted by Audio-Visual Media in an effort to improve the quality of learning on cognitive aspects and provide input for subsequent researchers to be able to increase creativity in carrying out the research process.